The real polysemous meaning of real: a study in lexical pragmatics - Olivier Simonin; Sarah Bourse (Lexis: Journal in English Lexicology)
Our main objective is to provide an account of the meaning of the polysemous adjective real that is theoretically grounded in post-Gricean pragmatics (Carston [2002], Recanati [2003], Sperber & Wilson [1996]). Combining lexical semantics and linguistic pragmatics is not new (see, e.g., Depraetere [2014] and Carston [2021]) and we believe that it can lead to a better understanding of the actual use of lexemes in context – especially when they are polysemous. Drawing on two pragmatic mechanisms, modulation and disambiguation (or lack thereof), we show how they interact with the lexical content of real and illustrate with genuine occurrences taken from ICE-GB (all of which we systematically annotated semantically). Little attention has been paid to the adjective real in the literature (with some exceptions: Bolinger [1972], Magnusson [2003]). Real is an untypical adjective. Its meaning is scalar when it causes a potentially gradable head noun (Filippi-Deswelle [2014], Moreau [2022]) to be semantically adjusted by indicating that a high (or high enough) degree is reached for a property or set or properties associated with that noun while, syntactically, it shows a very strong bias towards the attributive function – which we measure within ICE-GB and then explain.